Research on professional responsibility and ethics in accounting. Volume 23 - Baker, Charles Richard (Emerald Publishing Limited, 2020)
This edition of Research on Professional Responsibility and Ethics in Accounting includes articles from a distinguished group of authors. The topics cover many aspects of professional responsibility and ethics in accounting, including whistleblowing, professional skepticism, earnings management, cognitive style and ethics.